Phenotypic and whole genome-based characterization of antibiotic resistance of Campylobacter jejuni isolates from chicken livers - Alicia Manzanares-Pedrosa; Florencia Correa-Fiz; Fabián Andrade; Teresa Ayats; Miquel Nofrarías; Marta Cerdà-Cuéllar (Poultry Science, 2025)
Campylobacter is the leading cause of foodborne gastroenteritis worldwide with poultry and poultry products being major infection sources. Chicken livers may constitute a risk of infection due to their high Campylobacter prevalence. The growing presence of antibiotic resistant (AR) Campylobacter strains in poultry is a serious concern as they can be transferred to humans causing AR infections. This study assessed the AR prevalence of C. jejuni isolates from chicken livers from northeastern Spain. Using the broth microdilution method and whole-genome sequencing (WGS) with Illumina HiSeq, 39 liver isolates recovered from carcasses at slaughter from different farms were analyzed. Phenotypic AR to at least one out of six antibiotics tested was observed in 32 isolates (82 %). Ciprofloxacin (71.8 %) and tetracycline (64.1 %) were the most common resistances, and ciprofloxacin-tetracycline profile the most frequent (51.3 %). One isolate was multidrug resistant, while seven were susceptible to all tested antibiotics. Nearly all ciprofloxacin-resistant isolates carried the point mutation T86I in the gyrase gene, and most tetracycline-resistant isolates carried the tet(O) gene. All isolates carried genes coding for the CmeABC efflux pump, which may contribute to tetracycline resistance. The ertapenem-resistant isolate carried the blaOXA-185 gene, while almost all carried the blaOXA-61 which has been associated with β-lactam resistance. WGS analysis revealed additional potential resistance determinants, including genes associated with multidrug resistance, which were not detected phenotypically. Altogether, these results highlight the potential risk of chicken livers as a source of AR C. jejuni and underscore the added value of WGS in providing a deeper insight into the genotypic AR potential of these isolates.